Monitoring the sea change: Preliminary assessment of the conservation value of nearshore reefs, and existing impacts, in a high-growth, coastal region of subtropical eastern Australia - Smith, Stephen D.A.; Rule, Michael J.; Harrison, Matthew; Dalton, Steven J. (Marine pollution bulletin, 2008)
In northern NSW, Australia, coastal populations are forecast to increase dramatically over the next 25years (the “sea change”). However, management of the effects of development on marine communities is hampered by the lack of data on key habitats. Consequently, we developed a protocol to assess the biodiversity and current human impacts on nearshore reefs, habitats that will be readily affected by coastal development. We assessed four reefs adjacent to each of three population centres targeting fish, mollusc and sessile benthic communities, and debris loads. Community structure was highly variable over all spatial scales indicating that reefs should not be considered equivalent within the planning framework. While, debris loads were relatively low on most reefs, those with highest conservation value also had the highest debris loads suggesting potential conflict between human use and long-term sustainability of reefal communities. Without intervention, this situation will be exacerbated in the future.